Community pharmacy-based study of adherence to non-vitamin K antagonist oral anticoagulants. Issue 22 (23rd June 2020) - Capiau, Andreas; Mehuys, Els; Van Tongelen, Inge; Christiaens, Thierry; De Sutter, An; Steurbaut, Stephane; Moudallel, Souad; Rydant, Silas; Vrijens, Bernard; de Backer, Tine L M; Boussery, Koen
Abstract : Objective: This study aimed to assess implementation adherence (how well the patient's actual intake matches the prescribed dosing regimen) to non-vitamin K antagonist oral anticoagulants (NOACs) and to explore experiences with and beliefs about NOACs in a real-world sample of long-term NOAC users. Methods: A cross-sectional observational study was conducted in home-dwelling adults who started taking a NOAC at least 1 year prior to inclusion. Pharmacy dispensing data were used to calculate the Medication Possession Ratio (MPR). Patients were recruited in 158 community pharmacies in Flanders, Belgium. They completed a questionnaire collecting basic characteristics and exploring self-reported adherence to NOACs (using the Medication Adherence Report Scale, MARS) and experiences with and beliefs about NOACs (using the Beliefs about Medicines Questionnaire, BMQ). Results: A total of 766 patients (mean age 76.2±8.8 years, median CHA2 DS2 -VASc score 4 (IQR=3–4)) were included. The majority (93.5%) used NOAC for stroke prevention in atrial fibrillation. The median MPR was 95.2% (IQR=87.8–99.7) which corresponds with half of the study population not taking their NOAC on at least 17 cumulative days per year. Almost 21% of participants reported non-adherence on the MARS (score <25), with unintentional non-adherence (forgetfulness) most frequently reported (15.4%). Although two-thirds of NOAC users indicated to experience adverse drug reactions, the BMQ demonstrated a positive attitude towards NOAC therapy, where necessity beliefs outweigh the concerns. Conclusions: Our data indicate that long-term NOAC users have high implementation adherence and a positive attitude towards NOAC therapy. However, taking into account patients' thromboembolic risk and NOACs' short half-lives, further optimisation of NOAC use seems warranted in this population.